2021
DOI: 10.32598/jhnm.31.3.2070
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Husbands' ‌Awareness of Menopausal Complications on Physical Psychological Experiences of Postmenopausal Women

Abstract: Introduction: ‏ Women are subject to extensive changes during menopause. ‏Life crises such as menopause can affect women's health and is a turning point in their lives. ‏The husbands are the most important and closest people who can support their wives in this evolutionary crisis with their correct understanding of the situation. ‏Objective: ‏This study aimed to determine the effectiveness of husbands' ‏awareness of the physical and psychological experiences of postmenopausal women. Materials and Methods: ‏T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…A study by Shariat-Moghani et al, in which husbands of postmenopausal women received educational programming regarding menopause and its complications, resulted in a decrease in negative menopause-related experiences by their spouses [ 10 ]. This study along with others confirms that increasing family awareness and support improves women’s experiences and psychological and physical health [ 11 , 26 , 28 ]. Another approach is to educate the pre-and peri- menopausal women themselves as most have limited knowledge about menopause, its symptoms, and management and often are interested to learn more about the topic [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…A study by Shariat-Moghani et al, in which husbands of postmenopausal women received educational programming regarding menopause and its complications, resulted in a decrease in negative menopause-related experiences by their spouses [ 10 ]. This study along with others confirms that increasing family awareness and support improves women’s experiences and psychological and physical health [ 11 , 26 , 28 ]. Another approach is to educate the pre-and peri- menopausal women themselves as most have limited knowledge about menopause, its symptoms, and management and often are interested to learn more about the topic [ 29 , 30 ].…”
Section: Discussionsupporting
confidence: 84%
“…Menopause, with its many complications, has adverse effects on the quality of life of women and places strain on their relationships, especially with their partners [ 9 , 26 ]. A study by Currie and Moger which surveyed women 45 years of age or greater with menopause symptoms and their partners found that the physical and emotional effects of menopause affect women’s social life, professional lives, and relationships [ 27 ].…”
Section: Discussionmentioning
confidence: 99%